2004
DOI: 10.1038/sj.emboj.7600386
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin promotes endothelial cell proliferation and TGF-β/ALK1 signal transduction

Abstract: Endoglin is a transmembrane accessory receptor for transforming growth factor-beta (TGF-beta) that is predominantly expressed on proliferating endothelial cells in culture and on angiogenic blood vessels in vivo. Endoglin, as well as other TGF-beta signalling components, is essential during angiogenesis. Mutations in endoglin and activin receptor-like kinase 1 (ALK1), an endothelial specific TGF-beta type I receptor, have been linked to the vascular disorder, hereditary haemorrhagic telangiectasia. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
587
4
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(640 citation statements)
references
References 47 publications
38
587
4
4
Order By: Relevance
“…Studies have shown that signalling of TGFβ/ALK1–Smad1/5 stimulates EC migration and proliferation 48. Inhibition of endoglin in ECs, which is a part of the TGFβ receptor complex, potentiates TGFβ/ALK1 signalling,49, 50 resulting in reduced proliferation 51, 52. TGFβ binds to its specific receptors including TGFβR3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that signalling of TGFβ/ALK1–Smad1/5 stimulates EC migration and proliferation 48. Inhibition of endoglin in ECs, which is a part of the TGFβ receptor complex, potentiates TGFβ/ALK1 signalling,49, 50 resulting in reduced proliferation 51, 52. TGFβ binds to its specific receptors including TGFβR3.…”
Section: Discussionmentioning
confidence: 99%
“…Endoglin serves as an auxiliary receptor for TGF‐β signaling and is predominantly expressed in proliferating ECs and in tissues undergoing angiogenesis 37. Endoglin promotes ALK1‐mediated Smad1/5 signaling and inhibits ALK5‐mediated Smad2/3 signaling, leading to enhanced EC proliferation and angiogenesis 17, 18, 38, 39. Inhibiting endoglin expression by specific knockdown inhibits TGF‐β/ALK1 signaling and potentiates TGF‐β/ALK5 signaling,40, 41 resulting in reduced proliferation 19.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation or abnormal expression of endoglin is the etiological reason for hereditary hemorrhagic telangiectasia or preeclampsia, respectively, which are closely related to malformation and dysfunction of blood vessels 14, 15. Inhibiting endoglin by gene knockdown in ECs inhibits TGF‐β/ALK1 signaling, and potentiates TGF‐β/ALK5 signaling,16, 17, 18 resulting in reduced proliferation 17, 19. In contrary, endoglin overexpression suppresses TGF‐β/ALK5 signaling 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells, endoglin associates at the cell surface with the type I and type II TGF-b receptors and has a key role in modulating downstream signaling to the Smad transducer proteins (Guerrero-Esteo et al, 2002;Lebrin et al, 2004). The importance of endoglin acting as a TGF-b co-receptor in these events is evidenced by the observation that mutations in either ENG or the type I receptor ALK1 give rise to the vascular disorder hereditary hemorrhagic telangiectasia (McAllister et al, 1994;Johnson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%